Graphitization of polymer surfaces by scanning ion irradiation - Koval, Yury (Applied Physics Letters, 2014)
Graphitization of polymer surfaces was performed by low-energy Ar and He ion irradiation. A method of scanning irradiation was implemented. It was found that by scanning ion irradiation, a significantly higher electrical conductivity in the graphitized layers can be achieved in comparison with a conventional broad-beam irradiation. The enhancement of the conductance becomes more pronounced for narrower and better collimated ion beams. In order to analyze these results in more detail, the temperature dependence of conductance of the irradiated samples was investigated. The results of measurements are discussed in terms of weak localization corrections to conductance in disordered metals. The observed effects can be explained by enlargement of graphitic patches, which was achieved with the scanning ion irradiation method.